Syirik Dalam Kehidupan Modern: Bahaya Yang Tak Terduga Dan Solusi Masa Kini - Muhammad Agam Nalf Saujani; Rafif Hartawan Mukmin; Renita Ratriana; Dhea Nadila Violita; Rahma Dhita Syakirah; Fayzah Atsariyya; Muhamad Parhan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
In modern life, shirk has become a phenomenon that affects both individuals and society as a whole. The purpose of this research is to learn more about the unforeseen threats caused by committing shirk in everyday life. The article identifies the root causes of modern shirk, emphasizes its relevance in a social and spiritual context, and offers constructive solutions to deal with it using an analytical approach of theory and empirical facts. This method is expected to enhance understanding of the complexities of modern shirk and the importance of knowing its negative impact. The results of this analysis indicate that in responding to the challenges of shirk in modern life, preventive measures and appropriate interventions are required from both individuals and society.